Analisis Teori Hubungan Kausalitas dalam Hukum Pidana (Studi Putusan Pengadilan Negeri Atambua Nomor 140/Pid.B/2016/PN.ATB) - Aemili Rara Marcia Indriastuti; Emy Handayani; Mas’ut (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2025)
Causal relationships refer to cause-and-effect connections, where an event or phenomenon can serve as the cause or trigger for the occurrence of another event or phenomenon; this is one form of inductive reasoning. Inductive reasoning is used to draw a general conclusion from specific factual events. Regarding the application of causal relationship theories to the events in the Atambua District Court Decision Number 140/Pid.B/2016/PN.ATB, there are several differences in determining the causal factors of an outcome, namely the victim's death. Generally, the factor considered as the cause by causal relationship theories is the sixth factor. Exceptions include the conditio sine qua non theory, which regards all factors as causes, and the subjective adequacy theory, which also takes the second factor into account.